Sistem Cerdas Pemantauan Pergerakan Bus Wisata Ngulisik Kota Tasikmalaya - Siti Maesaroh; Rudi Hermawan; Dewanto Rosian Adhy; Sutrismawati Lingga Dewi; Akpil Mauhib; Asep Mustopa (TEMATIK, 2023)
The city of Tasikmalaya has the "Ngulisik" tourist bus, which wants to provide a pleasant tourist experience, but there are service problems in the service and efficiency of the route schedule and routes used. In-depth research is needed to analyze the problems and movements of Ngulisik tourist buses in order to create a tourism ecosystem that can serve user needs and is efficient in the service process provided. Another problem is arrival and departure times, as well as waiting times for tourists. The aim of this research is to collect, analyze, and visualize bus movement data to improve service efficiency, including aspects of routes, density, and correct bus route times. In this research, the process of installing a GPS tracker on the Ngulisik Tourism bus fleet is carried out, which is connected to a server to unify movements and obtain useful data for later analysis related to recommendations for tourist route packages and predictions of passenger density. The results of this research found that the Ngulisik tourist bus had the highest demand, with an average of 23 routes on Saturdays and Sundays, 10–15 routes on Wednesdays and Fridays, and less than 10 routes on Mondays, Tuesdays, and Thursdays, whereas the use of the 3 routes served by the Ngulisik tourist bus shows that 57% of the route use is less effective, causing a mismatch between demand and the route services provided.